1997
DOI: 10.2166/wst.1997.0057
|View full text |Cite
|
Sign up to set email alerts
|

A full-scale test of a biological nutrients removal system using the sequencing batch reactor activated sludge process

Abstract: A full-scale pilot plant using SBR process was experimented with an actual wastewater emanating from a recreational center. The main purpose of this investigation was to evaluate applicability in the field and process removal efficiencies in terms of BOD, SS, TN and TP and its corresponding kinetic parameters. It was found that removal efficiencies were comparable with results of other studies reported in the literature. BOD removal was observed to be 95% on average while SS removal to be 89% on average. Remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The HRT of CYCLE 2 was 7 h and 45 min. Better removal efficiencies for all parameters were obtained in CYCLE 2 with shorter total aerobic sequences than in previous studies in the literature (except first cycle of [22]), which is shown in Table 5. That study did not include denitrification but did have an anoxic sequence.…”
Section: Discussionsupporting
confidence: 49%
“…The HRT of CYCLE 2 was 7 h and 45 min. Better removal efficiencies for all parameters were obtained in CYCLE 2 with shorter total aerobic sequences than in previous studies in the literature (except first cycle of [22]), which is shown in Table 5. That study did not include denitrification but did have an anoxic sequence.…”
Section: Discussionsupporting
confidence: 49%
“…More than 98% removal of N and P has been achieved from piggery wastewater by optimizing cycle time and process modeling intended for better understanding of reactor behavior 29. Significant P removal can also be attained by using PAOs capable of denitrification in a single‐sludge system coexisting with nitrifers 30…”
Section: Simultaneous Nitrogen and Phosphorus Removalmentioning
confidence: 99%
“…The conventional anaerobic-aerobic processes incorporating an anoxic zone for denitrification have been used for N and P removal in full-scale wastewater treatment plants [41]. Significant P removal can also be attained by using DPAOs in a single sludge system coexisting with nitrifiers [42]. Studies were carried out using an anaerobic-aerobic-anoxic-aerobic system for simultaneous removal of nitrogen and phosphorus, and some important control strategies were suggested so that the DPAO are not inhibited [43].…”
Section: Simultaneous Removal Of Nitrogen and Phosphorus In An Sbr Prmentioning
confidence: 99%